Peningkatan Hasil Belajar Pai Melalui Metode Index Card Match Siswa Kelas V UPTD SDN 05 Suliki - Wirna Wirna; Iswantir Iswantir; Defi Yuslia; Roza Elfira; Imelda Sofia; Alpinadri Alpinadri (Jurnal Pendidikan Tuntas, 2024)
Education aims to increase the quantity and quality of students. In the learning process, the selection of the right learning method greatly affects the high and low learning outcomes of students. The learning method is a way that can be done by educators so that the teaching and learning process runs effectively. The problem in this study is the low learning outcomes of students in the subject of Islamic Religious Education. because the learning methods used are still not varied enough. To overcome this problem, the researcher applied the Index Card Match method with the aim of improving Islamic Religious Education learning outcomes in class V students of V UPTD SDN 05 Suliki. This study uses the type of classroom action research (CAR). The subjects in this study were 10 students in grade V of UPTD SDN 05 Suliki consisting of 4 male students and 6 female students. Classroom action research was carried out in two cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it showed that the average learning outcomes of students had increased. It is known that the KKM value that has been determined by the school is 75. In the pre- study, it was known that 3 students had not completed it with a percentage of 30% and 7 students had completed it with a percentage of 70%. In cycle I, there was an increase of 6 students who completed it with a percentage of 60% and 4 students who had not completed it with a percentage of 40%. Furthermore, in cycle II, there was an increase of 9 students with a percentage of 90% and 1 student who had not completed it with a percentage of 10%. Thus, the Index Card Match method can improve students' learning outcomes in Islamic Religious Education subjects at UPTD SDN 05 Suliki